Arduino based humidity and temperature sensor logger for environment monitoring - Miskon, Nur Wahida (2013)
This project is to develop a Humidity and Temperature Sensor Logger and Monitoring using Arduino. The device is used to measure and store data of temperature and relative humidity of target area. Using this system, monitoring is performed automatically so that no manual operation to the instruments is applied during whole period of monitoring. The three pins on the sensor connect the two devices. The pins are inserted into the Arduino through the two-wire digital serial interface, and digital data is transmitted here. The Arduino will be programmed with the specific Arduino software. After the setup a coding is inputted to Arduino boot loader chip and the sensor is ready to be run and measure. It will read out the humidity and temperature values which then are stored into the SD card and displayed on the LCD. Based on the sensor, the accuracy of the temperature should be within ±2⁰C, while the relative humidity is ±5%.